PENINGKATAN MINAT MENGGUNAKAN JASA KOPERASI SYARIAH MELALUI MODEL EDUKASI KONSUMEN (SURVEY UMKM KOTA BANDUNG) - Siska, Nurhayati; Budhi, Pamungkas; Krishna, Yuliawati (Jurnal Ilmiah Manajemen & Bisnis, 2017)
ABSTRACT The number of cooperatives in West Java, including the three largest in Indonesia as many as 25.563 units in 2014.However, growth in the number of cooperatives, was not followed by the public interest to become members of the Cooperative. Based on Compass Survey 2015, only 17% of respondents were interested in becoming members of the cooperativeBased on the gap between the number of cooperatives that continue to increase, but the public interest to become members of the cooperative are low, then the study was conducted. The research objective was to determine the factors supporting and hindering SMEs to become members of cooperatives sharia. By using a reference Theory of Planned Behavior (TPB) to formulate the determinants of interest MSMEs become members of cooperatives sharia. These factors will be used to construct a model of consumer education.Descriptive method used to describe the SMEs. Collecting data using the techniques of observation, interviews and questionnaires.The results showed the determinant of the greatest interest to encourage the interest of SMEs are eligible members of sharia is the Evaluation of Behavior Beliefs, followed by the Normative Beliefs, Behavioral Beliefs, and Motivation to Comply. And determinants of interest that become an obstacle MSMEs to become cooperative members sharia is Control Beliefs and Perceived Power. Interest in the SME entrepreneurs to become members of the cooperative is high enough.